Effect of adipose mesenchymal stem cell-derived exosomes on allergic rhinitis in mice - Xiaojie Xu; Chang Li; Qin Qin; Feiyan Han; Ying Wang (Heliyon)
Background: At present, the treatment for allergic rhinitis (AR) is only limited to symptom relief, and AR is not able be cured. It is important to find new therapeutic regimens for AR. Objective: To explore the effect of adipose mesenchymal stem cell-derived exosomes (AMSC-exos) on AR in mice. Methods: Primary human AMSCs were cultured up to fourth or fifth passage AMSCs which were used to extract AMSC-exos by ultracentrifugation. The AMSC-exos were identified in size, morphology and surface marker proteins. AR mouse models were made, and then effects of the AMSC-exos on AR mouse models were observed by injection of AMSC-exos into their tail veins. A total of 21 mice were divided into normal mice with injection of phosphate buffered saline (PBS) group (Normal + PBS group, 7 mice), AR mice with injection of AMSC-exos group (AR + AMSC-exos group, 7 mice) and AR mice with injection of PBS (AR + PBS group, 7 mice). After injection of AMSC-exos and PBS, symptoms were observed in mice and inflammatory factors including IL-4, IL-5, IFN- γ and Ig-E were determined. Mice were sacrificed, nasal mucosa was collected for HE staining and qRT-PCR. Results: After injection of AMSC-exos, compared with the AR + PBS group, symptoms were significantly improved, inflammatory factor levels were significantly decreased, disturbed and thickened mucosal layer was relieved, and the numbers of goblet cells and eosinophils were reduced in the AR + AMSC-exos group. Conclusion: AMSC-exos can improve symptoms and inflammatory level in the AR mice.